Automatic Generation Control of Multi-Area Solar-Thermal Power System Using Fruit-Fly Optimization Algorithm - V.S.Acharyulu, B.; K.Hota, P.; Mohanty, Banaja (International Journal of Engineering and Technology, 2018)
In this paper, fruit-fly optimization algorithm (FOA) is applied to automatic generation control (AGC) of multi-area power systems. In the proposed three-area system, reheat thermal systems are considered in all areas incorporating solar thermal power plant (STPP) in one of the areas. The optimum gain of proportional-integral-derivative (PID) controller is optimized applying FOA technique. The strength of FOA is established by comparing the results with well-established Grey Wolf optimizer (GWO) technique for the same interconnected power system. The performances of the system with FOA technique are found to be better than GWO algorithm for both with and without incorporating STPP in area-1. Further, from the sensitivity analysis, it is evident that the PID controller gains obtained by FOA technique under normal conditions are found to be better even for large changes in slip and system load conditions.Â Â